Klinefelter Syndrome in Association with Tetralogy of Fallot and Congenital Diaphragmatic Hernia - Swaminathan, Sethuraman; Gorla, Sudheer R.; Barbouth, Deborah S. (Journal of Pediatric Genetics, 2017)
Klinefelter syndrome (KS) is the most common sex chromosomal aneuploidy in males. Major cardiovascular and diaphragmatic anomalies are uncommon in this syndrome. Here we report an infant with KS who had tetralogy of Fallot and congenital diaphragmatic hernia, all of which were identified prenatally and managed successfully after birth. Microarray analysis did not reveal any deletions or duplications other than the additional X-chromosome, to account for the additional abnormalities in this infant. To the authors' knowledge, this is the first such report of major cardiac and diaphragm anomaly occurring together, in an infant with KS.
Keywords: Klinefelter syndrome; tetralogy of Fallot; congenital diaphragmatic hernia